“A Most Delightfully and Carefully Translated Book”. Problems of Translating Proper Nouns on the Exaple of the Polish Translation of the Evocations of Italy by Pavel Muratov - Fryźlewicz, Halszka (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2024)
This article deals with the little researched topic of the translation of an art history essay. The Polish translation by Paweł Hertz of Pavel Muratov’s “Evocations of Italy” served as the material for analysis. The context of the work’s publication in Poland is presented at the outset. In the following part of the article the basic translation problems related to the translation of ekphrasis are listed: translation of terms from the fine arts, calque, and loanwords. Most of all, however, paper focuses on the problem of translating proper nouns, especially titles of works of art, defined by the term “artionym”. On the basis of selected examples, it was concluded that this is an important translation problem, requiring the translator to be familiar with the literature on the subject, as individual works may have many different titles.